Parodies of Didactic Victorian Verses in Slovene Translations of Alice’s Adventures in Wonderland - Kaloh Vid, Natalia (Slavia Centralis, 2022)
The current analysis focuses on how Carroll’s parodies of famous didactic Victorian poems in Alice’s Adventures in Wonderland were rendered by Slovene translators. The humourist effect in these parodies is based on a mockery of socially accepted norms and Victorian protocol, as well as on the deconstructing of the moral and didactic principles of the Victorian Era, an epoch which the target audience of Slovene children or adults barely know. The primary goal of the research is to analyse strategies Slovene translators used to re-create the parodied effect, and how these solutions influenced the readers’ interpretative abilities, impression, and understanding of Carroll’s text, considering that parodied poems were unknown in the target Slovenian culture. I was particularly interested whether (and in which way) the translators ensured the familiar parody effect, and what happened to the double meanings commonly found in parodies.
Keywords: Alice’s Adventures in Wonderland; Lewis Carroll; translation; parody; Russia; Slovene